PID Fuzzy Logic Controller System for DC Motor Speed Control - M., H. Samsul Bachri (Makara Journal of Technology, 2004)
PID Fuzzy Logic Controller System for DC Motor Speed Control. A good controller system must have resilience to disturbance and must be able to response quickly and accurately. Problem usually appears when PID controller system was built sensitively hence the system’s respon to the disturbance will yield big overshot/undershot then the possibility of oscillation to be happened is excelsior. When the controller system was built insensitively, the overshot/undershot will be small but the recovery time will be longer. Hybrid controller system could overcome those problems by combining PID control system with fuzzy logic. The main control of this system is PID controller while the fuzzy logic acts to reduce an overshot/undershot and a recovery time. The fuzzy logic controller is designed with two input error and delta error and one output of the motor speed. The output of fuzzy logic controller should be only half of the PID controller for limiting entirely fuzzy output. This hybrid system design has a better respon time controller system than PID controller without fuzzy logic.